Prediction of rainfall in Kuala Lumpur / Hurun Ain Mohd Roslan, Siti Syakirin Sazali and Haslinda Ab Malek - Mohd Roslan, Hurun Ain; Sazali, Siti Syakirin; Ab Malek, Haslinda (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Rainfall is one of the most important elements of weather patterns. It is an essential atmospheric phenomenon and influential meteorological parameter in many aspects of daily life (Elvis Selase, 2015). The frequency and amount of rainfall have long been acknowledged as having an impact on the environment, economy, society, and even biodiversity. It is a significant factor and one of the most challenging problems on global and local weather atmospheric circulation. Generally, rainfall events can begin or end at any time of the day and may last a few hours or several days. The main types of rainfall are orographic, frontal or cyclonic and convectional. Convectional rainfall, frontal rainfall occurs due to what happens when a cold front meets a warm front. Meanwhile, orographic rainfall occurs on the upwind sides of the mountain ranges (Team, 2022). Figure 1 illustrates the information of orographic, frontal and convectional rainfall.